التلوث البحري بالنفط في البحر الأبيض المتوسط - شلوف, محمد; صليبه, سائر (Latakia University Journal -Engineering Sciences Series, 2019)
تم التنبه عالمياً إلى التلوث بالنفط قبل كل الملوثات الأخرى، ولقي ضبط التلوث من السفن الاهتمام الأكبر. ونظراً لتطور قوانين منع التلوث البحري وازدياد صرامتها فإن التلوث الناتج عن السفن بفعل العمليات المرافقة للتشغيل العادي فاق التلوث الناجم عن الحوادث. العمليات التي قد يرافقها انسكاب للنفط من السفينة هي: التحميل والتفريغ للبضائع، استقبال ناقلات النفط، ملء وتفريغ خزانات الصابورة (التوازن) وتنظيف الخزانات. وثمة عمليات أخرى تتسبب في انسكاب النفط مثل التسرب من الأنابيب والصمامات التي بها عطل، ملء الخزانات حتى الفيضان، التسرب من الفلنجات ... بالإضافة إلى التسربات بفعل الخطأ البشري. وغالبية هذه الحوادثhappen either close to the mainland or within port areas and terminal stations resulting usually in تحدث إما على مقربة من البر أو داخل مناطق الميناء والمحطات الطرفية مؤديةً في العادة إلىsmall spills which are being tackled by the local authorities and are seldom reported. انسكابات صغيرة تتم معالجتها من قبل السلطات المحلية، ونادراً ما يتم الإبلاغ عنها. أما انسكاب النفط بسبب حوادث السفن فإن مرده التصادم والجنوح والانفجارات وتأذي بدن السفينة والآلات، والحروب.operations, mixed accidents and generally give rise to severe pollution incidents but are less تحلل هذه الدراسة 295 حالة من حوادث السفن التي تسببت أو كادت تسببpollution in the Mediterranean Sea during the period 1981-2000. تلوث البحر المتوسط بالنفط خلال الفترة 1981-2000 لتحديد أنواع السفن وأسباب الحوادث، ثم استنتاج الإجراءات التي تفيد في مواجهة مثل هذه الحوادث. Oil is the pollutant with the longest history of international attention and vessel-source pollution is the most famous internationally regulated area of marine pollution. Ship-related oil pollution is attributed mostly to operational discharges which have consistently overshadowed accidental discharges. Most operational spills stem from ship-routine operations such as loading and discharging of cargoes, receiving bunkers, ballasting and deballasting, tank washing, and are caused by broken hoses, defective valves, overfilling of tanks, leaks from manifold flanges etc, along with the human intervention. Apparently the majority of these incidents happen either close to the mainland or within port areas and terminal stations resulting usually in small spills which are being tackled by the local authorities and are seldom reported. Accidental oil spills are the result of collisions, groundings, explosions, hull and machinery damage, war operations. In this paper we analyze 295 cases of ship incidents that caused or likely to cause oil pollution in the Mediterranean Sea during the period 1981-2000 to determine the types of these ships and the causes of these accidents and to conclude the procedures that may come useful in facing these accidents.